The Critical Incident Technique: An Innovative Qualitative Method of Research - Woolsey, Lorette K (Canadian Journal of Counselling and Psychotherapy, 2011)
The critical incident technique is an exploratory qualitative method of research that has been shown both reliable and valid in generating a comprehensive and detailed description of a content domain. After being used widely in industrial psychology during the 1950's, the technique fell into diverse and is only now enjoying a renaissance. The critical incident technique basically consists of asking eyewitness observers for factual accounts of behaviours (their own or others') which significantly contribute to a specified outcome. The emphasis is on incidents (things which actually happened and were directly observed) which are critical (things which significantly affected the outcome). This paper tells how to do a critical incident study, using illustrations from the author's and others' research. The many and varied applications of the technique are indicated. These uses range from criterion development and test construction to foundational work and theory development. It is concluded that the critical incident technique should contribute significantly to the development of a unique methodology for the discipline of counselling.